Factors Related to Stress Class XII Students Of Public High School at Bekasi, West Java - Agustina Yulisa Palayukan; Stefanus Andang Ides; Sudibyo Supardi (Healthy-Mu Journal, 2023)
Stress is a pressure that occurs due to a mismatch between the expected situation and reality when there is a gap between environmental demands and the individual's ability to fulfill them. In Indonesia, the number of adolescents who experience stress increase every year. Data from RISKESDAS by the Indonesian Ministry of Health in 2013 was 6.0% and increased to 9.8% in 2018. This study aims to determine the relationship between gender, parenting, and the economic level of parents with stress levels in students. This study uses a descriptive correlational research method with random sampling technique. Respondents in this study were final year  students of SMAN 9 Bekasi in the academic year 2021-2022. Bivariate data analysis was using the Chi-Square test. The results showed that the gender of the respondents was 61,6% female, the parenting style of the respondents was 47.7% authoritarian, the economic level of the respondents was 65.1% in the very high category and the stress level of the respondents was 68.8% in the moderate stress level. The results of the bivariate analysis showed that there was a significant relationship between gender (p-value = 0.022) and stress levels. But there was no relationship between parenting style (p-value = 0.494) and economic level (p-value = 0.484) on the level of stress.